Branding emocional para el sector lácteo del cantón Quero - Arnaldo Paúl Pozo Valle (2024)
The Tungurahua Dairy Consortium (CONLAC-T) is an entity that markets around miles of liters of milk per month to companies such as El Ranchito, AGSO, El Ordeño and Paraíso, at a reduced cost per liter. This association operates with nine milk collection centers and brings together 1,150 small farmers. For this reason, it was proposed to use the emotional branding strategy, since it allows companies to shorten the distance with their target audience. The purpose of the project is to propose emotional strategies to promote the positioning of dairy brands. Surveys were used to understand the tastes and preferences of consumers in Quero, and interviews to investigate the characteristics and perceptions of CONLAC-T members. Likewise, knowledge about emotional branding was deepened by consulting experts, with the intention of generating relevant criteria on the topic. A didactic game-tool designed specifically for dairy producers was applied where recognition, emotion and brand management were promoted. Various data were obtained with the members of the association regarding the ideal graphic image with specific emotions and colors for their own brand, in addition to knowing the current perspective of the market from their vision. Finally, based on the results found, a manual was prepared that summarizes and specifies the functional emotional branding strategies for the dairy sector guided by all the knowledge acquired in the project, using simple language for the target audience.